Squeezed states phase space representation and semiclassical approximations in many-body systems - Mizrahi, S. S.; Galetti, D. [UNESP] (Elsevier, 1990)
We derive an alternative semiclassical approach (to the Wigner-Kirkwood method) for many-body systems using a mapping scheme based on the squeezed states phase space representation. The new expansion is applied to the usual harmonic oscillator case and the differences with the Wigner-Kirkwood results are discussed. © 1990.